Acetyl-coenzyme A synthetase 2 is a nuclear protein required for replicative longevity in Saccharomyces cerevisiae - Falcón, Alaric A. (2009)
Acs2p is one of two acetyl-coenzyme A synthetases in Saccharomyces cerevisiae. We have prepared and characterized a monoclonal antibody specific for Acs2p and find that Acs2p is localized primarily to the nucleus, including the nucleolus, with a minor amount in the cytosol. We find that Acs2p is required for replicative longevity: an acs2Δ strain has a reduced replicative life span compared to wild-type and acs1Δ strains. Furthermore, replicatively aged acs2Δ cells contain elevated levels of extrachromosomal rDNA circles, and silencing at the rDNA locus is impaired in an acs2Δ strain. These findings indicate that Acs2p-mediated synthesis of acetyl-CoA in the nucleus functions to promote rDNA silencing and replicative longevity in yeast.